X-ray Diffraction Studies and its Application on the Examination of Defect and Growth Mechanism of some Laser Host Materials - J, Podder,; T, Hossain, (Malaysian Journal of Science, 2002)
Crystallization of non-linear optical (NLO) single crystals has become an important field of research in recent years in view of industrial applications in modern optical and optoeletronics devices for the efficient processin of optical signals. Potassium dihydrogen phosphate (KPD), urea, ammonium oxalate (AO) etc. are the well-known non-linear optical materials and have vast applications in the solid-state laser source devics. The laser source materials KPD and AO have been grown from low temperature aqueous solutions with the addition of different mole concentration of urea and some rare earth impurities like La, Sm, Gd to improve the quality of the crystal and their non-linear optical properties. X-ray diffraction studies were carried out on the grown single crystal using a Shimadzu X-ray Diffractometer with CuKÃŽÂ± radiation. X-ray study reveals that the structures of the doped crystals were slightly distorted compared to the pure crystal. From the X-ray diffraction pattern, the 2ÃŽÂ¸, 'd'-spacing and relative intensity values for the corresponding hk1 values were calculated. The deviation in 2ÃŽÂ¸ (i.e. ÃŽâ€2ÃŽÂ¸ Ã¢â€°Â¡ 2ÃŽÂ¸$_Exp$ = 2ÃŽÂ¸$_Cal$) for the experimental and calculated values suggests that the structures are slightly distorted. this may be attributed to strain on the lattice by the adsorption of impurities. The lattice constant values are found to be varied with the addition of impurity concentrations and satisfy the Vegard's law.